Tensile strains in concrete. - Blakey, F. A. (Frank A.) (Report C (CSIRO. Division of Building Research) ;, 1953)
Extensive tensile strain measurements have been made on various types of unreinforced surface-dry concrete specimen under simple and complex stress conditions. The tests have made possible a comparison of the performances of A.C. and D.C. equipment with electrical resistance strain gauges, and have given information on the tensile behaviour of concrete which suggests that fracture does not take place instantaneously as it is usually considered to do in brittle materials.